Hubungan Lama Hemodialisa Dengan Care Dependency Pada Pasien Gagal Ginjal Kronik Yang Menjalani Terapi Hemodialisis Di Rsud Dr. Abdoer Rahem - Wahyuni, Ida; Tri Nili Sulayfiyah; Mery Eka Yaya Fujianti; Rohman, Atiqur; Bergita Dumar (Universitas Nazhatut Thullab Al- Muafa Sampang, 2024)
Background: Chronic kidney failure can cause psychological, physical and social activity disorders. Therapy that can preserve the kidneys is hemodialysis. Purpose: This study aims to determine the relationship between duration of hemodialysis and care dependency in CKD patients undergoing hemodialysis therapy. Care dependency was measured using the Care Dependency Scale (CDS). Method: The design of this research is descriptive quantitative with a cross sectional approach. The variables in this study are duration of hemodilsis and care dependency. The research sample was 109 respondents taken using a consecutive sampling technique. Data were analyzed using the Chi Square test. Results: The research results show that there is no relationship between the length of hemodialysis and care dependency with a p value > 0.05, which means there is no relationship between care dependency and the length of hemodialysis. Conclusions: Patients who have been undergoing hemodialysis for a long time will tend to have mild or moderate levels of stress, because of the length of time undergoing hemodialysis, patients are able to adapt themselves to the dialysis equipment and hemodialysis patients will find it easier to manage physical limitations in their daily lives.